Red Beet Biotechnology 2012
DOI: 10.1007/978-1-4614-3458-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Potentials of Red Beet Pigments and Other Constituents

Abstract: Diabetes mellitus is a group of metabolic disorders characterized by elevated sugar levels in blood, caused by defects in insulin secretion and further signaling cascades. Among the approaches to overcome diabetes, diet plays a key role in the maintenance of blood sugar level, in the hyper-glycosylation of biomolecules associated with diverse metabolisms, and in the prevention of pathologies thus associated. In this connection, a number of bioactive molecules found in fruits, vegetables, dietary constituents, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
2
3
0
Order By: Relevance
“…Supporting our data, several lines of evidence have also shown the potent hypoglycemic, anti-inflammatory, and antioxidant potentials of beetroot juice or extracts in a variety of animal models [ 49 , 50 ]. Indeed, daily consumption of red beetroot juice extracts significantly reduced fasting glucose levels in diabetic individuals, as well as in STZ and alloxan-induced diabetic animals, effects that were attributed to increased insulin release (in T1DM), decreased glucose absorptions, stimulated insulin sensitivity, GLUT-2/4 receptor expression, and inhibited hepatic glucose synthesis [ 25 , 30 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Supporting our data, several lines of evidence have also shown the potent hypoglycemic, anti-inflammatory, and antioxidant potentials of beetroot juice or extracts in a variety of animal models [ 49 , 50 ]. Indeed, daily consumption of red beetroot juice extracts significantly reduced fasting glucose levels in diabetic individuals, as well as in STZ and alloxan-induced diabetic animals, effects that were attributed to increased insulin release (in T1DM), decreased glucose absorptions, stimulated insulin sensitivity, GLUT-2/4 receptor expression, and inhibited hepatic glucose synthesis [ 25 , 30 , 51 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 84%
“…These ingredients are known for their hypoglycemic, hypolipidemic, and antioxidant potential, and they can modulate numerous cells signaling with the cells they constitute; it is well established in the literature. This has been discussed in previous studies and reviews [ 49 , 50 , 60 ]. Moreover, further investigation is required to examine the precise molecular mechanisms responsible for the hypoglycemic, hypolipidemic, and antioxidant effects of the extract.…”
Section: Discussionmentioning
confidence: 75%
“…Since dyslipidemia and oxidative stress enhance insulin resistance [37], it seems that the anti-insulin resistance effect is related to the anti-hyperlipidemia and anti-oxidant effects of betanin. The anti-diabetic effects of red beet have been demonstrated in previous reports [25]. In this regard, the highest dose of betanin in the treated groups was more effective (compared with the protective mode).…”
Section: Discussionsupporting
confidence: 62%
“…In another study, trans-chalcone (12 mg/kg) did not decrease remarkably these parameters in obese mice [16]. Previous studies have demonstrated that components containing betanin such as djulis and red beet could reduce cholesterol, triglyceride and LDL levels and elevate levels of HDL [25,38,40]. Overall, betanin exerted beneficial anti-hyperlipidemic effects on the lipid profilein both treatment and protection mode.…”
Section: Discussionmentioning
confidence: 89%
“…Beet root contain high amounts of phenolic compounds, flavonoids, carotenoids and betalains, all of which have strong antioxidant and free radical scavenging activities Yanardag, 2010 &Panghal et al, 2017). Beet root possess hypoglycemic activity by increasing insulin sensitivity and lowering the activity of metabolic enzymes (Murthy andManchali, 2012 &Indumathi et al, 2017). As well as previous studies have indicated that red beet root can be used for therapy of renal disorders, where it alleviates renal disfunction and oxidative damage (EL Gamal et al, 2014 andHassan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%